Evaluating relationships between native fishes and habitat in streams affected by oil and natural gas development. (16th August 2018) - Girard, Carlin E.; Walters, Annika W.
Abstract: Oil and natural gas (ONG) development can affect aquatic ecosystems through water contamination, water withdrawals and disturbance of soil and vegetation (surface disturbance) from infrastructure development. Research on how these potential sources of watershed and aquatic ecosystem impairment can affect fish assemblages is limited. Fish–habitat relationships were evaluated across stream sites experiencing differing levels of ONG development. Colorado River cutthroat trout, Oncorhynchus clarkii pleuriticus (Cope), and mottled sculpin, Cottus bairdii Girard, presence and abundance were associated with habitat conditions predominantly found in the less disturbed streams, such as higher proportion of shrub cover, greater stream depths and gravel substrate. Mountain sucker, Catostomus platyrhynchus (Cope), appeared to be a habitat generalist and was able to persist in a wide range of conditions, including degraded sites. Natural resource managers can use habitat preferences of these fish species to establish the development plans that mitigate negative effects of ONG development by protecting the aquatic habitats they rely upon.